Ideario de un encuentro vital: Jacques Gilard y Marvel Moreno - Yohainna Abdala-Mesa (Caravelle)
This essay is an overview of the research that Jacques Gilard did on Marvel Moreno’s works. As reader, translator, a supporter and the literary trustee of the author’s work, Gilard’s stance was very different from that of the traditional critic. Beginning with his role in the dissemination of Moreno’s works and his presence in the early formation of the writer’s career, this study discusses his critical writings on Moreno and synthesizes his cultural and ideological contributions to the understanding of her work. Gilard’s conceptualization of the intellectual genesis of the author, his knowledge about the work in progress, his quest to avoid conventional analysis and his desire to leave research paths for the future generations of readers are some of the significant aspects commented.